(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article compares the available information about the life and work of Abu Mansur Moturidi, the founder of the doctrine of Moturidi, the great scholar of Ahl as-Sunnah, and clarifies many contradictions in this regard. In particular, various information about the birth and death of the scholar, his teacher and students, as well as his works were compared, and on the basis of evidence, an attempt was made to reveal the real truth. The sources do not specify the date of Abu Mansur Moturidi’s birth. Other information about scholar does not allow to determine this. That is why there are only assumptions in this regard. Information about other aspects of a scientist’s life and work also differs in the sources. This is because most of the information about the scientist’s identity dates back to a long time after the scientist’s death. Although it is not mentioned that Moturidi traveled in search of knowledge like most other scholars, he became a mature scholar of his time.This can be explained by the fact that at that time Samarkand was one of the centers of Islamic science, which gathered many mature scholars of their time. For this reason, there was no need for Moturidi to travel in search of knowledge. Abu Mansur Moturidi based his doctrine on the works narrated from Abu Hanifa and developed new issues based on them. During his research on these issues, the scientist sought to prove them with convincing evidence beyond doubt.The disciples and followers of the scholar played a major role in the development of the teachings of Moturidi. They brought the scholar’s works into book form, commented on them, and wrote new works based on Moturidi’s teachings.